THE EFFECT OF THE USE OF VOLUME CONSERVATION TOOLS ON STUDENT'S LEARNING OUTCOMES - Mariah Mariah; Ali Arridho (Universitas Muhammadiyah Lampung, 2023)
Education is the main factor that must be improved in quality, the progress of the civilization of a society or nation will lie in the level of education. To improve the quality of education in this case it is necessary to increase student learning outcomes, in studying science to achieve these goals, in the teaching and learning process there must be adequate situations and conditions as well as appropriate methods in learning that can have a positive effect on learning effectiveness in achieving goals. education. The method used in this study is a quantitative method, where the final score of the variable is in the form of numbers which are then processed using a statistical formula to produce a value. The population in this study were all students of class VIII at SMP Negeri 1 Padangcermin and the samples in this study were 40 students of class VIII A and 40 students of class VIII B of SMP Negeri 1 Padangcermin. To find out the results of this study, it was done by giving an essay test. From the results of the study, it can be concluded that there is an effect of the use of conservation of volume teaching aids on learning outcomes in class VIII even semester of SMP Negeri 1 Padangcermin where the average learning outcomes of students who use conservation of volume teaching aids are higher than the average learning outcomes of students who do not use props. volume conservation prop. Thus, learning that is accompanied by the use of conservation of volume props has a positive effect or can improve student learning outcomes.